The Influence of Earning Opacity and Tax Planning on Accrual Quality with Debt Cost As A Moderating Variable in Energy Sector Companies (Idxenergy) Listed on The Indonesia Stock Exchange From 2019-2022 - Tutik Siswanti; Etty Murwaningsari (Green Publisher Indonesia, 2025)
This study aims to measure the effect of earning opacity and tax planning on accrual quality with debt cost as a moderation variable in Energy Sector Companies (IDXENERGY) listed on the Indonesia Stock Exchange. The sample of this study is based on 184 annual observations of companies listed on IDX in Indonesia during the period 2019-2022. This study uses a panel regression model to test the hypothesis. The results show that earning opacity with proxi earning aggressiveness significantly affects the quality of accrual. Meanwhile, tax planning has no effect on the quality of accruals. Meanwhile, debt costs are not able to moderate the influence of earning opacity and tax planning on accrual quality. This study makes a significant contribution to the accounting literature on how earning opacity is a factor that can have an impact on the quality of accruals which can ultimately lead to the low quality of information produced by the company.